Assessment of a novel, 22-lead mobile electrocardiogram in elite, adolescent footballers - Johnson, H.; Duarte, N.; Ryding, D.; Perry, D.; McNally, S.; Stuart, A. G.; Williams, C. A.; Pieles, G. (International Journal of Sports Medicine, 2022)
The 12-lead electrocardiogram is a key component of cardiac screening in elite adolescent footballers. Current technology hampers mobile electrocardiogram monitoring that could reduce the time-to-diagnosis in symptomatic athletes. Recently, a 22-lead mobile electrocardiogram monitor, CardioSecur (Personal MedSystems GmbH), has been approved for use in adults. In this study, the differences in parameter accuracy between CardioSecur`s 22-lead electrocardiogram and the gold standard 12-lead electrocardiogram were assessed in elite adolescent footballers (n=31) using Bland-Altman and paired t-tests/Wilcoxon analysis. Agreement between the two devices was clinically acceptable for heart rate (bias=- 0.633 bpm), PR Interval (bias=- 1.73 ms), Bazzett`s corrected QTc interval (bias=2.03 ms), T-wave axis (bias=6.55°), P-wave duration (bias=- 0.941 ms), Q-wave amplitude (bias=0.0195 mV), Q-wave duration (bias=1.98 ms), rhythm (bias=0.0333), ST-segment (bias=- 0.0629), J-point analysis (bias=- 0.01) and extended T wave and QRS duration analysis. Unsatisfactory agreement was observed in QRS axis (bias=- 19.4°), P-wave axis (bias=- 0.670°), QRS amplitude (bias=- 0.660 mV), P-wave amplitude (bias=0.0400 mV) and T-wave amplitude (bias=- 0.0675 mV). CardioSecur`s 22-lead electrocardiogram agrees with the gold standard in rhythm, durations, T-wave determination in all leads assessed, permitting its use in adolescent footballers for immediate pitch- or track-side analysis.